Identifying research priorities in cardiac surgery: a report from the James Lind Alliance Priority Setting Partnership in adult heart surgery. Issue 9 (3rd September 2020) - Lai, Florence Y; Abbasciano, Riccardo G; Tabberer, Bethany; Kumar, Tracy; Murphy, Gavin J
Abstract : Objective: To identify research priorities that address the needs of people affected by cardiac surgery and those who support and care for them. Design: James Lind Alliance (JLA) process—two surveys and a consensus workshop guided by an independent JLA adviser. Setting: The UK with international participation. Participants: Three stakeholder groups—heart surgery patients, carers and healthcare professionals involved in care delivery. Methods: The initial survey was set to collect potential research questions in cardiac surgery as identified by stakeholders. Submitted questions were summarised into indicative questions. The existing evidence was searched to verify that these indicative questions had not been answered. In the second survey, stakeholders then voted for their top 10 from the list of unanswered questions. The top voted questions were taken forward for final ranking in a workshop. Results: In the initial survey, 629 respondents (28% patients/carers, 62% healthcare professionals) submitted 1082 potential questions. Of these, 797 in-scope questions were summarised into 49 indicative questions and of which 45 had not been answered by existing research. In the second survey, 492 respondents (43% patients/carers, 49% healthcare professionals) cast their votes with the top 12 from each of the three stakeholder groups totalling 21 questions advancing to the final priority setting workshop. The workshop attended by 25 delegates (10 patients/carers and 15 healthcare professionals) agreed on the top 10 research questions including long-term outcomes (quality of life), and aspects from preoperative personalised care (prehabilitation, frailty, comorbidities), intraoperative management (minimally invasive techniques), to prevention and management of postoperative complications (organ injury, atrial fibrillation, infection). Conclusions: This Priority Setting Partnership (PSP) identified the priorities and unmet needs of patients and clinicians in cardiac surgery. The next step is to disseminate and implement the PSP results to ensure that these priorities shape future research and improve clinical services.